2013
DOI: 10.1177/0743558413477199
|View full text |Cite
|
Sign up to set email alerts
|

Latina Mothers’ and Daughters’ Expectations for Autonomy at Age 15 (La Quinceañera)

Abstract: American children gain more autonomy as they progress through adolescence, however, autonomy-granting for Latina adolescent girls from immigrant families is a relatively unexplored question. In this study, we identified behaviors that Mexican mothers and their daughters deemed to be appropriate when they reach the age of La Quinceañera, a cultural rite of passage at age 15. Daughters hoped for rules regarding social activities to become less strict whereas mothers intended to continue to exert control, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
(83 reference statements)
0
20
0
3
Order By: Relevance
“…A limitation with this study was the mismatch between the guiding framework (SDT) and the type of autonomy described by mothers (PI). A study of low‐income Mexican American mothers of 15‐year‐old girls indicated that mothers granted independence to adolescents in terms of decision making about physical appearance and group dating, but they continued to exert control in peer and social activities, household chores, and homework responsibilities (Romo, Mireles‐Rios, & Lopez‐Tello, ). These findings suggest that whereas Mexican American parents engage in autonomy support in the form of decision making, that support often occurs in combination with controlling and protective parenting practices.…”
Section: Autonomy‐supportive Parenting and Culturementioning
confidence: 99%
“…A limitation with this study was the mismatch between the guiding framework (SDT) and the type of autonomy described by mothers (PI). A study of low‐income Mexican American mothers of 15‐year‐old girls indicated that mothers granted independence to adolescents in terms of decision making about physical appearance and group dating, but they continued to exert control in peer and social activities, household chores, and homework responsibilities (Romo, Mireles‐Rios, & Lopez‐Tello, ). These findings suggest that whereas Mexican American parents engage in autonomy support in the form of decision making, that support often occurs in combination with controlling and protective parenting practices.…”
Section: Autonomy‐supportive Parenting and Culturementioning
confidence: 99%
“…Assim, é possível que, nesta amostra, os pais insistam mais nas regras relacionadas à segurança e a comportamentos socialmente esperados, contribuindo para que os filhos obedeçam-nas, mesmo não concordando. Ao mesmo tempo, considerando que pais e filhos estão vivenciando o iní-cio da adolescência destes, é importante que as regras também sejam ajustadas, havendo maior flexibilidade, por exemplo, quanto às regras a respeito de horários e do uso de seu tempo livre (Romo et al, 2013).…”
Section: Discussionunclassified
“…Apesar disso, é comum que o relato de adolescentes e pais sobre essa temática seja discrepante. Em geral, os adolescentes reportam ter mais desejo de autonomia do que seus pais concedem (Daddis, 2011;Romo, Mireles-Rios, & Lopez-Tello, 2013;Rote & Smetana, 2014) e se percebem como mais autônomos e competentes para lidar com ela do que seus pais os percebem (Butner et al, 2009).…”
unclassified
“…different social roles due to developmental stages of adults vs. their children). Mothers may continue to exert more control over their daughters who are yearning for greater autonomy (Romo et al 2014). This struggle for independence can even contribute to escalating aggression in girls, including aggression between daughters and mothers (Chesney-Lind 2004;Chesney-Lind and Brown 1999;Letendre 2007).…”
Section: Encouraging Mother-daughter Relationshipsmentioning
confidence: 97%